Community-based physical activity-related health promotion in Germany Systematic review and good practice projects - Dippon, Lea; Helsper, Natalie; Kohler, Simone; Weber, Philipp; Rütten, Alfred; Pfeifer, Klaus; Birkholz, Leonie; Semrau, Jana (German Journal of Exercise and Sport Research, 2023)
Approaches to community-based physical activity-related health promotion (CPAHP) are recommended to counteract physical inactivity in the population. The aim of this article was to present a systematic review of CPAHP measures in Germany. Furthermore, we aimed to identify good practice projects to provide guidance for the implementation and scale up of CPAHP. In the first step, we identified projects by searching 4 scientific databases and 21 project databases. We then extracted data for "federal state ", "consideration of health equity " and "implementation in urban or rural areas ". In addition, we sorted the included projects into different approaches in the community setting. In the next step, we assessed projects with a documented process and/or outcome evaluation using quality criteria for the phases of conceptualization, implementation, and evaluation. Projects that fulfilled at least 50% of the quality criteria were selected as good practice projects. We identified a total of 240 CPAHP projects. Rural areas primarily implemented environmental approaches, while urban areas focused more on multicomponent approaches as well as offers and events. Overall, 45 projects showed adequate documentation of the process and/or outcome evaluation, of which 17 projects were identified as good practice. However, there is potential for improvement in addressing health equity, active participation of socially disadvantaged people over the entire project cycle, and implementation of multicomponent approaches. This requires funding programs that promote good-practice projects which establish structures and particularly reach disadvantaged communities. A jointly adopted standard by stakeholders from policy, practice, and research for the application of quality criteria along with a classification for good practice would be beneficial for further strategic development of CPAHP in Germany.
CRIS-Team WoS Importer:2023-03-17

Co-producing an action-oriented framework for community-based Physical Activity Promotion in Germany - Kohler, Simone; Helsper, Natalie; Dippon, Lea; Rütten, Alfred; Abu-Omar, Karim; Pfeifer, Klaus; Semrau, Jana (Health promotion international, 2021)
German National Recommendations for Physical Activity (PA) and PA Promotion recommend community-based approaches to promote PA at the local level with a focus on health equity. In addition, the German Federal Prevention Act addresses health equity and strengthens setting-based health promotion in communities. However, the implementation of both in the local context remains a challenge. This article describes Phase 1 of the KOMBINE project that aims to co-produce an action-oriented framework for community-based PA promotion focusing on structural change and health equity. (i) In a series of workshops, key stakeholders and researchers discussed facilitators, barriers and needs of community-based PA promotion focusing on health equity. (ii) The research team used an inductive approach to cluster all findings and to identify key components and then (iii) compared the key components with updated literature. (iv) Key components were discussed and incorporated into a gradually co-produced framework by the participants. The first result of the co-production process was a catalog of nine key components regarding PA-related health promotion in German communities. The comparison of key components with scientific evidence showed a high overlap. Finally, a six-phase action-oriented framework including key components for community-based PA promotion was co-produced. The six-phase action-oriented framework integrates practice-based and scientific evidence on PA-related health promotion and health equity. It represents a shared vision for the implementation of National Recommendations for PA and PA Promotion in Germany. The extent to which structural changes and health equity can be achieved is currently being investigated in pilot-studies.
Keywords: physical activity promotion; community; recommendations; implementation

Co-Producing an Action-Oriented Framework for the Implementation of the German National Recommendations for Physical Activity and Physical Activity Promotion. - Kohler, Simone; Dippon, Lea; Helsper, Natalie; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (24th IUHPE World Conference on Health Promotion., 2022)

Development of a Framework for Scaling Up Community-Based Health Promotion: A Best Fit Framework Synthesis - Weber, Philipp; Birkholz, Leonie; Kohler, Simone; Helsper, Natalie; Dippon, Lea; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (International Journal of Environmental Research and Public Health, 2022)
Community-based health promotion with a focus on people with social disadvantages is essential to address persistently existing health inequities. However, achieving an impact on public health requires scaling up such approaches beyond manifold funded pilot projects. The aim of this qualitative review is to provide an overview of scaling-up frameworks in health promotion and to identify key components for scaling up community-based health promotion. First, we conducted a systematic search for scaling-up frameworks for health promotion in PubMed, CINAHL, Scopus, Web of Science, PsycInfo, and SportDiscus. Based on the included frameworks, we created an a priori framework. Second, we searched for primary research studies in the same databases that reported scaling-up processes of community-based health promotion. We coded the data using the a priori framework. From 80 articles, a total of 12 frameworks were eligible, and 5 were included for data extraction. The analysis yielded 10 a priori defined key components: “innovation characteristics”; “clarify and coordinate roles and responsibilities”; “build up skills, knowledge, and capacity”; “mobilize and sustain resources”; “initiate and maintain regular communication”; “plan, conduct, and apply assessment, monitoring, and evaluation”; “develop political commitment and advocacy”; “build and foster collaboration”; “encourage participation and ownership”; and “plan and follow strategic approaches”. We further identified 113 primary research studies; 10 were eligible. No new key components were found, but all a priori defined key components were supported by the studies. Ten key components for scaling up community-based health promotion represent the final framework. We further identified “encourage participation and ownership” as a crucial component regarding health equity.
CRIS-Team Scopus Importer:2022-04-29
Keywords: community; health equity; health promotion; physical activity promotion; scaling up

Erprobung eines Handlungsmodells zur Umsetzung kommunaler Bewegungsförderung - Kohler, Simone; Dippon, Lea; Helsper, Natalie; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (Kongress Armut und Gesundheit 2022, 2022)

Faktoren der nachhaltigen Umsetzung kommunaler Bewegungsförderung bei Menschen mit sozialer Benachteiligung: eine systematische Übersichtsarbeit - Semrau, Jana; Helsper, Natalie; Kohler, Simone; Janz, Lukas; Abu-Omar, Karim; Rütten, Alfred; Pfeifer, Klaus (Sport im öffentlichen Raum. Abstractband des 24. dvs-Hochschultags von 18. bis 20. September 2019 in Berlin., 2019)
Einleitung § 20a SGB V zielt auf die nachhaltige Verankerung von Gesundheitsförderung in Lebenswelten. Dies umfasst auch die Entwicklung nachhaltiger Konzepte der kommunalen Bewegungsförderung (kBF) bei Menschen mit sozialer Benachteiligung (MmsB). Das Ziel hier ist die Identifikation von Faktoren für die nachhaltige Umsetzung von kBF bei MmsB. Methode Es wurde eine systematische Übersichtsarbeit mit narrativer Synthese erstellt. Die Suche erfolgte in den Datenbanken Pubmed, Scopus, CINAHL, PsycINFO/SportDiscus und WebofScience in englischer und deutscher Sprache bis 09/2018. Es wurden qualitative, quantitative, "mixed-method" Studien, Reports und Reviews berücksichtigt. Artikel wurden eingeschlossen, wenn sie Faktoren der Nachhaltigkeit populationsbezogener Ansätze der Bewegungsförderung im kommunalen Kontext bei MmsB (z.B. mit sehr niedrigem Einkommen, sozialem Status) untersuchten. Eligible Studien wurden anhand des Rahmenmodells von Schell et al. (2013) analysiert. Ergebnisse Es wurden 29 Studien (13 qualitative, 1 quantitative, 9 "mixed-method" Studien, 3 Reviews, 3 Berichte) eingeschlossen. Es konnten 137 Nennungen zu Faktoren der Nachhaltigkeit identifiziert werden. In Anlehnung an Schell et al. (2013) werden Faktoren am häufigsten in den Domänen Kapazitäten auf organisatorischer Ebene (21), Partnerschaften (18) und Stabilität in der Förderung (16) berichtet. Ergänzend wurden weitere Faktoren in den Bereichen Zugangswege (11), Infrastruktur (7), Partizipation (9) und kultureller Kontext (10) ermittelt. Diskussion Die identifizierten Faktoren zur Förderung der Nachhaltigkeit sollten bereits frühzeitig bei der Konzeption von Maßnahmen der kBF bei MmsB systematisch adressiert werden. <br
Keywords: Nachhaltigkeit; Bewegungsförderung; Kommune; soziale Benachteiligung

Implementation of a Framework for Community-Based Physical Activity Promotion with a Focus on Structural Change and Health Equity - Dippon, Lea; Helsper, Natalie; Kohler, Simone; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (24th IUHPE World Conference on Health Promotion, 2022)

Implementierung eines Handlungsmodells für kommunale Bewegungsförderung zur Umsetzung der Nationalen Empfehlungen - Dippon, Lea; Helsper, Natalie; Kohler, Simone; Pfeifer, Klaus; Rütten, Alfred; Semrau, Jana (Sport, Mehr & Meer – Sportwissenschaft in gesellschaftlicher Verantwortung. Abstractband des 25. dvs-Hochschultages, Kiel / virtuell, 29.–31. März 2022, 2022)

Implementing the German National Recommendations for Physical Activity and Physical Activity Promotion: A project overview - Dippon, Lea; Kohler, Simone; Helsper, Natalie; Abu-Omar, Karim; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (Proceedings of the 8th International Society for Physical Activity and Health (ISPAH) Congress, 2021)

Implementing the German National Recommendations for Physical Activity and Physical Activity Promotion: Results Phase-1. - Kohler, Simone; Helsper, Natalie; Dippon, Lea; Abu-Omar, Karim; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (Proceedings of the 8th International Society for Physical Activity and Health (ISPAH) Congress, 2021)

KOMBINE: Kommunale Bewegungsförderung zur Implementierung der Nationalen Empfehlungen mit Fokus auf Menschen mit sozialer Benachteiligung - Semrau, Jana; Kohler, Simone; Helsper, Natalie; Janz, Lukas; Abu-Omar, Karim; Rütten, Alfred; Pfeifer, Klaus (Umweltmedizin, Hygiene, Arbeitsmedizin, 2019)
Zielsetzung KOMBINE zielt auf die Implementierung der Nationalen Empfehlungen für Bewegung und Bewegungsförderung in der Lebenswelt Kommune (Pfeifer & Rütten, 2017). Dabei stellt die Erreichbarkeit von Menschen mit sozialer Benachteiligung eine besondere Herausforderung dar (Lorenc et al. 2013). Ziele der Phase I waren daher a) die partizipative Entwicklung eines Handlungsmodells für die bevölkerungsbezogene Bewegungsförderung mit Fokus auf Menschen mit sozialer Benachteiligung sowie b) die Auswahl von Modellkommunen zur Erprobung des Handlungsmodells. Methode Zur Erhebung der praktischen Evidenz wurden zwei Workshops und zwei AG-Treffen in vier Monaten durchgeführt. Parallel wurde die wissenschaftliche Evidenz zur a) Wirksamkeit und b) Nachhaltigkeit populationsbezogener Ansätze der Bewegungsförderung mit Fokus auf Menschen mit sozialer Benachteiligung recherchiert. Die Integration der Evidenz bildete die Basis für die Entwicklung des Handlungsmodells. Die Auswahl von sechs Modellkommunen erfolgte sowohl auf Basis systematischer Kriterien wie geographische Lage, Gemeindegröße, Strukturstärke und Vorerfahrungen als auch pragmatischer Aspekte. Ergebnis 64 Praxisvertreter*innen aus 43 Kommunen sowie 21 nationale Entscheidungsträger*innen willigten zur Teilnahme ein. Im Workshop 1 erfolgte die Einteilung in drei Arbeitsgruppen. Die Teilnehmer*innen identifizierten 100 Erfolgsfaktoren, 74 Barrieren und 96 Bedarfe für die populationsbezogene Bewegungsförderung in der Kommune. Daraus wurden induktiv 10 Schlüsselkomponenten abgeleitet, mit den Arbeitsgruppen validiert und in ein dreistufiges Handlungsmodell eingeordnet. Im nächsten Schritt wurde das Modell auf sechs Stufen erweitert. Auf dem Workshop 2 wurde das finale Handlungsmodell verabschiedet. Zur Erprobung des Handlungsmodells in Phase II wurden drei Landkreise, eine mittlere Stadt, eine Großstadt und eine Metropole ausgewählt. Schlussfolgerung Die frühzeitige Einbindung kommunaler Akteure und nationaler Entscheidungsträger*innen erscheint für eine wirksame und nachhaltige Umsetzung kommunaler Bewegungsförderung mit Fokus auf Menschen mit sozialer Benachteiligung erfolgversprechend. In Phase II werden aktuell das Handlungsmodell kontextspezifisch erprobt und entsprechende Wirkungen evaluiert.<br

KOMBINE - Municipal Physical Activity Promotion for the Implementation of the National Recommendations News from the six Model Municipalities - Helsper, Natalie; Dippon, Lea; Kohler, Simone; Abu-Omar, Karim; Pfeifer, Klaus; Rütten, Alfred; Semrau, Jana (Bewegungstherapie und Gesundheitssport, 2020)
CRIS-Team WoS Importer:2020-12-18

KOMBINE - Municipal Physical Activity to Implement National Recommendations - Semrau, Jana; Helsper, Natalie; Janz, Lukas; Kohler, Simone; Abu-Omar, Karim; Pfeifer, Klaus; Rütten, Alfred (Bewegungstherapie und Gesundheitssport, 2019)
CRIS-Team WoS Importer:2019-08-09

Kommunale Bewegungsförderung bei Menschen mit sozialer Benachteiligung: ein partizipativer Ansatz der Koproduktion - Semrau, Jana; Kohler, Simone; Helsper, Natalie; Janz, Lukas; Abu-Omar, Karim; Rütten, Alfred; Pfeifer, Klaus (Sport im öffentlichen Raum. Abstractband des 24. dvs-Hochschultags von 18. bis 20. September 2019 in Berlin, 2019)
Einleitung Das KOMBINE-Projekt zielt auf die Implementierung der Nationalen Empfehlungen für Bewegung und Bewegungsförderung in der Lebenswelt Kommune (Pfeifer & Rütten, 2017). Ziel der ersten Projektphase war die Entwicklung eines Handlungsmodells für die bevölkerungsbezogene Bewegungsförderung bei Menschen mit sozialer Benachteiligung auf Basis eines Ansatzes der Koproduktion. Methode Zur Erhebung der praktischen Evidenz wurden zwei Workshops und zwei AG-Treffen in vier Monaten durchgeführt. Parallel wurde die wissenschaftliche Evidenz zur a) Wirksamkeit und b) Nachhaltigkeit populationsbezogener Ansätze der Bewegungsförderung mit Fokus auf Menschen mit sozialer Benachteiligung anhand von zwei Reviews recherchiert. Die Integration der Evidenz bildete die Basis für die Entwicklung des Handlungsmodells. Ergebnisse 64 Praxisvertreter aus 43 Kommunen sowie 21 nationale Entscheidungsträger willigten zur Teilnahme ein. Im Workshop 1 erfolgte die Einteilung in drei Arbeitsgruppen. Die Teilnehmer identifizierten 100 Erfolgsfaktoren, 74 Barrieren und 96 Bedarfe für die populationsbezogene Bewegungsförderung in der Kommune. Daraus wurden induktiv 10 Schlüsselkomponenten abgeleitet, mit den Arbeitsgruppen validiert und in ein dreistufiges Handlungsmodell eingeordnet. Im nächsten Schritt wurde das Modell auf sechs Stufen erweitert. Auf dem Workshop 2 wurde das finale Handlungsmodell verabschiedet. Diskussion Die frühzeitige Einbindung kommunaler Akteure und nationaler Entscheidungsträger scheint für eine wirksame und nachhaltige Umsetzung kommunaler Bewegungsförderung erfolgversprechend. Die Erprobung des Handlungsmodells von KOMBINE erfolgt in Phase 2 in sechs Modellkommunen. <br
Keywords: Kommune; Bewegungsförderung; Koproduktion; soziale Benachteiligung

Kommunale Bewegungsförderung zur Implementierung der Nationalen Empfehlungen – KOMBINE-Manual: Praxisleitfaden - Kohler, Simone; Dippon, Lea; Helsper, Natalie; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (2021)

Multi-level stakeholders' perspectives on implementation and scaling up community-based health promotion in Germany - Birkholz, Leonie; Weber, Philipp; Helsper, Natalie; Kohler, Simone; Dippon, Lea; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (Health promotion international, 2023)
Community-based health promotion has the potential to address existing health inequities, although such approaches are scarcely scaled up. For a successful scale up, various stakeholders at different levels and sectors need to be involved. The article's aims are to assess what kind of external support communities need for implementation and to identify facilitators and barriers for scaling up community-based health promotion. Two national digital workshops were conducted in Germany with stakeholders at the community level (n = 161) and with stakeholders at the federal and state levels (n = 84). Protocols were compiled and coded using qualitative content analysis. During the first workshop, we revealed 11 themes for external support needs ('Strategic approach', 'Define & compare indicators', 'Internal human resource', 'Tools & Aids', 'External conduction of the assessment', 'Involvement of people in difficult life situations', 'Overview of actors', 'Moderation', 'Obtain funding', 'Quality assurance/evaluation' and 'External support'). Eleven facilitators and barriers were identified for scaling up ('Assessment and evaluation', 'Intersectoral collaboration and partnerships', 'Communication', 'Characteristics of the program', 'Political and legal conditions', 'Political support', 'Local coordinator', 'Resources', 'Participation', 'Strategic planning/methods' and 'Intermediary organization'). The identified results provide practice-based evidence on support needed for scaling up, facilitators that promote scaling up and barriers that might hinder scaling up community-based health promotion in Germany. In a next step, this practice-based evidence needs to be systematically integrated with scientific-based evidence on key components for scaling up such approaches for the development of an effective scaling-up concept.
CRIS-Team WoS Importer:2023-05-26
Keywords: health promotion; community; implementation; scaling up

O3-1 Key factors for sustainable implementation of community-based physical activity promotion with a focus on individuals with social disadvantages: a systematic review with narrative synthesis - Helsper, Natalie; Semrau, Jana; Kohler, Simone; Dippon, Lea; Abu-Omar, Karim; Rütten, Alfred; Pfeifer, Klaus (EUROPEAN JOURNAL OF PUBLIC HEALTH, 2022)
Background According to the German prevention law (§ 20a SGB V) of 2016, statutory health insurances are legally bound to integrate sustainable setting-based health promotion in their activities. This includes the development of sustainable concepts for community-based physical activity promotion (cbPAP) with a focus on socially disadvantaged individuals (SDI) (e.g. individuals with low income, low social status) to improve health equity. The aim of the systematic review with a narrative synthesis is to identify context-specific factors for the sustainable implementation of cbPAP and further, to inform the project KOMBINE (German acronym for ‘Community-Based PA Promotion to Implement National Recommendations’) for a scientific and practice-based implementation of the National Recommendations for Physical Activity and Physical Activity Promotion in communities. Methods A systematic review with narrative synthesis was conducted. The search was carried out in the databases PubMed, Scopus, CINAHL, PsycINFO/SportDiscus, and WebofScience. Searches were limited to only include studies published up until 04/2020, in English and German. Altogether, qualitative, quantitative, “mixed-method” studies, reports and reviews were considered. Articles referring to factors of sustainable implementation of community-based physical activity promotion with a whole-system approach were included. Although this was not an inclusion criterion, articles addressing accessibility for SDI were specifically taken into account. The framework by Schell et al. (2013) was used for data extraction and analysis, while the four main elements from Popay et al. (2006) were applied in the narrative synthesis process. Results 29 studies (13 qualitative, 1 quantitative, 9 “mixed-method” studies, 3 reviews, 3 reports) were included in the review. 137 references to sustainability factors were identified. According to the framework by Schell et al. (2013), factors were most frequently reported in domains of organizational levels (21), partnerships (18) and financial stability (16). Additional factors in the domains of accessibilities for SDI (11), infrastructure (7), participation (9), and cultural context (10) were identified by the authors. The relationship between the factors and the context of the programs are considered as well. Conclusions The identified factors for sustainability should be systematically addressed at an early stage in the conception of cbPAP measures for SDI to ensure sustainability after implementation.
CRIS-Team WoS Importer:2022-09-23
Keywords: sustainability; physical activity promotion; community; social disadvantage

P08-05 Community-based interventions to promote physical activity among individuals with social disadvantages - Kohler, Simone; Semrau, Jana; Helsper, Natalie; Dippon, Lea; Abu-Omar, Karim; Pfeifer, Klaus; Rütten, Alfred (European Journal of Public Health, 2022)
CRIS-Team WoS Importer:2022-09-23

Population-based physical activity promotion with a focus on health equity: a review of reviews - Kohler, Simone; Dippon, Lea; Helsper, Natalie; Rütten, Alfred; Abu-Omar, Karim; Birkholz, Leonie; Pfeifer, Klaus; Weber, Philipp; Semrau, Jana (International Journal For Equity in Health, 2023)
Background: The extent to which people are physically active is dependent upon social gradients. Numerous studies have shown that especially people with social disadvantages do not meet the physical activity (PA) recommendations. A promising strategy to alleviate this issue are approaches that promote PA in the general population. In addition, several researchers have raised concerns that population-based health interventions may increase health inequities. The aim of the current review of reviews was therefore to identify successful population-based PA promotion approaches with a particular focus on health equity. Methods: Six electronic databases were examined for systematic reviews on population-based PA promotion for the period 2015 to 2021. A reference list and grey literature search were also conducted. Two independent reviewers used inclusion/exclusion criteria to screen titles and abstracts of the potentially relevant literature and conducted a quality assessment for each identified review. All included reviews of population-based approaches for PA promotion with a focus on disadvantaged populations and/or health equity were narratively summarized. Results: Our search resulted in 4,411 hits. After a systematic review process, six reviews met the inclusion criteria and were included after they were all rated as high quality. We identified that mass-media campaigns, point-of-decision prompts, environmental approaches, policy approaches, and community-based multi-component approaches can promote PA in the general population. Across populations with social disadvantages mass-media campaigns, point-of-decision prompts and policy approaches are likely to be effective as long as they are tailored. Regarding environmental approaches, the results are inconsistent. None of the reviews on community-based multi-component approaches provided evidence on health equity. Conclusion: There are several effective approaches to promote PA in the general population but evidence regarding health equity is still sparse. Future studies should therefore pay more attention to this missing focus. Furthermore, there is a lack of evidence regarding the type of tailoring and the long-term impact of population-based approaches to PA promotion. However, this requires appropriate funding programmes, complex study designs and evaluation methods.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Health equity; Health promotion; Physical activity; Population-based approaches; Social disadvantages

Practice-based evidence for scaling up community-based health promotion: national and local perspectives - Weber, Philipp; Birkholz, Leonie; Dippon, Lea; Kohler, Simone; Helsper, Natalie; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (24th IUHPE World Conference on Health Promotion, 2022)
Background/Objectives To achieve effective and sustainable implementation of community-based physical-activity-related health promotion with a focus on health equity, an approach that integrates the existing scientific and practice-based evidence was developed and tested in 6 communities in Germany. To scale up this approach, an appropriate concept is needed that is also scientifically grounded and considers different practice-based experiences. Therefore, this study aims to assess the practice-based knowledge of community and national stakeholders for the development of a scaling up concept for community-based physical activity-related health promotion. Methods Two national digital workshops were conducted in March and April 2021. Community stakeholders (n=163) were involved in the first workshop to identify, where communities need support and what they can accomplish themselves to implement community-based physical activity-related health promotion. In the second workshop, national stakeholders from the sport, health, and social sector as well as researchers (n=92) discussed facilitators and barriers for scaling up health promotion interventions. The discussions were transcribed and coded using qualitative content analysis. Results Most themes that emerged during the first workshop showed that while several communities needed support for a specific aspect other communities stated to have the appropriate resources for the same aspect. However, most stakeholders mentioned the need for external process support or a strategic concept. The involvement of various stakeholders was seen as an effort that communities can best manage themselves. During the second workshop, national stakeholders emphasized that transregional networks and intermediate organizations were crucial success factors for scaling up, whereas a lack of intersectional cooperation and scarce financial resources were cited as barriers. Discussion The involvement of stakeholders at local as well as national level was an important step for scaling up this approach and implementation in the communities. The various themes shed light on the practice-based evidence on scaling up community-based health promotion. Together with scientific evidence on key components for scaling up community-based approaches to promote physical activity, a science- and practice-based scaling up concept will be developed and tested in 12 communities throughout German

„Practice-based evidence“ in der kommunalen Bewegungsförderung: Entwicklung einer Suchstrategie zur Recherche von Praxisprojekten - Janz, Lukas; Helsper, Natalie; Kohler, Simone; Semrau, Jana; Abu-Omar, Karim; Rütten, Alfred; Pfeifer, Klaus (Sport im öffentlichen Raum. Abstractband des 24. dvs-Hochschultags von 18. bis 20. September 2019 in Berlin, 2019)
Einleitung Im Projekt KOMBINE, soll ein Überblick vorhandener Projekte der kommunalen Bewegungsförderung mit Fokus auf Menschen mit sozialer Benachteiligung in Deutschland gegeben werden. Mit standardisierten Suchstrategien in wissenschaftlichen Literaturdatenbanken werden jedoch vorwiegend wissenschaftliche Projekte ermittelt (Reis et al., 2016). Zur Erfassung von praxisbezogenen und wissenschaftlichen Projekten, wurde deshalb eine alternative Suchstrategie entwickelt und erprobt. Methode Ziel der Suchstrategie war es, alle relevanten Projekte zu identifizieren und dabei methodische Hürden (z. B. Google-Filter-Bubble) von Suchmaschinen, zu überwinden. Entwickelt wurde die Suche mittels Strategieansätzen und Problemlösungen aus wissenschaftlichen Arbeiten, welche durch eine Recherche identifiziert wurden. Die gesammelten Erkenntnisse wurden an den Kontext und den Zielen der Suche angepasst. Ergebnisse Die Suchstrategie ist in fünf Schritte gegliedert: (1) Zunächst wurden mit einer Suche via startpage.de, 40 Datenbanken identifiziert. (2) Aktuell werden diese nach Projekten gescreent. Die Projektliste wird anschließend von einer (3) systematischen Suche in wissenschaftlichen Literaturdatenbanken, einem (4) Screening der Literaturverzeichnisse und abschließend von einer (5) iterativen Projektsuche via startpage.de ergänzt. Eingeschlossen werden Projekte der kommunalen Bewegungsförderung in Deutschland, welche strukturbezogene Maßnahmen beinhalten. Diskussion Die alternative Suchstrategie konnte methodische Hürden wie z. B. der Filter Bubble teilweise überwinden und hat sich als nützliches Instrument zur Erfassung von praxisbezogenen und wissenschaftlichen Projekten erwiesen.<br
Keywords: Kommune; Bewegungsförderung; Qualitätsanalyse; Praxisprojekte

Praxisbasierte Evidenz für die Verbreitung und Umsetzung kommunaler Bewegungsförderung: nationale und lokale Perspektiven - Weber, Philipp; Dippon, Lea; Helsper, Natalie; Birkholz, Leonie; Kohler, Simone; Pfeifer, Klaus; Rütten, Alfred; Semrau, Jana (Sport, Mehr & Meer – Sportwissenschaft in gesellschaftlicher Verantwortung. Abstractband des 25. dvs-Hochschultages, Kiel / virtuell, 29.–31. März 2022, 2022)
Um eine wirksame und nachhaltige Implementierung von kommunaler Bewegungsförderung zu erreichen, wurde ein Interventionsansatz entwickelt, der vorhandene wissenschaftliche und praxisbasierte Erkenntnisse integriert (Kohler et al., 2021). Nach der Erprobung in sechs Modellkommunen in Deutschland wird für die Verbreitung dieses Ansatzes ein geeignetes Konzept benötigt, das wissenschaftlich fundiert ist und unterschiedliche Praxiserfahrungen berücksichtigt. Für die Entwicklung dieses Verbreitungs- und Umsetzungskonzepts erfasst diese Studie praxisbasiertes Wissen von kommunalen und überregionalen Akteurinnen und Akteuren. Im März und April 2021 wurden zwei nationale digitale Workshops durchgeführt. Am ersten Workshop nahmen kommunale Akteurinnen und Akteure (n = 163) teil, um Unterstützungsbedarfe für die Umsetzung kommunaler Bewegungsförderung zu ermitteln. Im zweiten Workshop diskutierten überregionale Stakeholder*innen aus dem u. a. Sport-, Gesundheits- und Sozialbereich sowie Wissenschaftler*innen (n = 92) über Förderfaktoren und Hindernisse für die Verbreitung von kommunaler Bewegungsförderung. Die Diskussionen wurden transkribiert und mittels qualitativer Inhaltsanalyse ausgewertet. Im ersten Workshop formulierten kommunale Akteurinnen und Akteure Unterstützungsbedarf im Sinne einer externen Prozessberatung und für ein strategisches Gesamtkonzept zur Umsetzung kommunaler Bewegungsförderung. Während des zweiten Workshops betonten die Teilnehmer/-innen, dass überregionale Netzwerke und intermediäre Organisationen entscheidende Erfolgsfaktoren für die Verbreitung sind, während mangelnde intersektorale Zusammenarbeit als Hindernis angeführt wurde. Die Aktivierung von Akteurinnen und Akteuren auf lokaler und überregionaler Ebene war ein wichtiger Meilenstein für die Verbreitung des Interventionsansatzes und dessen Umsetzung in den Kommunen. Zusammen mit wissenschaftlichen Erkenntnissen zu Schlüsselkomponenten der Verbreitung kommunaler Bewegungsförderung wird ein wissenschafts- und praxisbasiertes Verbreitungs- und Umsetzungskonzept entwickelt und in Deutschland erprob
Keywords: Verbreitung; kommunale Bewegungsförderung; intergierte Evidenz

Researchers as Policy Entrepreneurs for Structural Change: Interactive Research for Promoting Processes Towards Health Equity - Rütten, Alfred; Semrau, Jana; Helsper, Natalie; Dippon, Lea; Kohler, Simone; Pfeifer, Klaus (Springer International Publishing, 2022)
Health promotion is understood as a “strategy” for social change towards better health for all. Certain structures of social practices persistently preserve health inequalities. By acting as “policy entrepreneurs,” researchers can orient and support a change of such structures towards health equity. At the same time, this enables researchers to co-produce new knowledge on these fundamental processes. Using a case example from the field of physical activity (PA) promotion in Germany, necessary conditions of policy entrepreneurship are described. We point out how “policy windows of opportunities” were identified and used by a group of researchers. The approach presented builds on an interactive-knowledge-to-action methodology systematically linking research practice with the practices of policymakers, professionals, and population groups. The case study indicates how research practice could bridge national policies and recommendations with the practices of local communities. It outlines how various stakeholders co-produced a conceptual framework for health promotion innovation and subsequently setting it into innovative practice in six German pilot communities. Finally, the challenges and achievements of the presented approach will be discussed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Cooperative planning; Health equity; National recommendations; Physical activity; Policy entrepreneurship; Structural change

S11 Improving knowledge co-creation and participation in physical activity promotion: The cooperative planning approach - Gelius, Peter; Sommer, Raluca; Ferschl, Susanne; Till, Maike; Abu-Omar, Karim; Semrau, Jana; Helsper, Natalie; Kohler, Simone; Dippon, Lea; Pfeifer, Klaus; Rütten, Alfred; Popp, Johanna; et al. (EUROPEAN JOURNAL OF PUBLIC HEALTH, 2022)
CRIS-Team WoS Importer:2022-09-23

Scaling up community-based physical activity-related health promotion – a best fit framework synthesis - Birkholz, Leonie; Weber, Philipp; Dippon, Lea; Kohler, Simone; Helsper, Natalie; Pfeifer, Klaus; Rütten, Alfred; Semrau, Jana (24th IUHPE World Conference on Health Promotion, 2022)
Background/Objectives Community-based health promotion with a focus on structural change towards better “health for all” is essential to address persistently existing health inequities. However, achieving a public health impact requires the scaling up of this approach beyond manifold funded pilot projects. In the field of physical activity-related health promotion only few community-based approaches have been implemented on a larger scale. Thus, the aim of this systematic review is to provide an overview of scaling up frameworks for community-based health promotion, and to identify key components for successfully scaling up community-based approaches to promote physical activity. Methods We followed the “best fit” framework synthesis approach. Firstly, we conducted a search for scaling up frameworks for community-based health promotion in PubMed, CINAHL, Scopus, Web of Science, PsycInfo, and SportDiscus. Then, we created an a priori framework based on the included frameworks. Secondly, we searched for primary research studies in the same databases with an additional grey literature search using Google Scholar. We searched for studies that report on scaling up processes of community-based physical activity promotion. The data were coded using the identified a priori framework. Results From 80 articles, a total of 12 studies were eligible and reported on 12 scaling up frameworks. We included 5 frameworks for data extraction. This yielded into 10 a priori defined key components: innovation characteristics; clarify and coordinate roles and responsibilities; build up skills, knowledge, and capacity; mobilize and sustain resources; initiate and maintain regular communication; plan, conduct and apply assessment, monitoring, and evaluation; develop political commitment and advocacy; build and obtain collaborations; encourage participation and ownership; plan and follow strategic approaches. We further identified 113 primary research studies with a total of 10 eligible studies. No new key components were found, but all a priori defined key components were supported by the studies. Discussion The “best fit” framework synthesis approach provides science-based insights for developing successful scaling up processes in the field of physical activity-related health promotion. The results will be used to develop a science- and practice-based concept for scaling up a community-based physical activity approach together with stakeholders from the national and community level.

Schlüsselkomponenten für die Verbreitung bewegungsbezogener Gesundheitsförderung - Birkholz, Leonie; Weber, Philipp; Dippon, Lea; Helsper, Natalie; Kohler, Simone; Pfeifer, Klaus; Rütten, Alfred; Semrau, Jana (Sport, Mehr & Meer – Sportwissenschaft in gesellschaftlicher Verantwortung. Abstractband des 25. dvs-Hochschultages, Kiel / virtuell, 29.–31. März 2022, 2022)
Gesundheitsförderung in der Lebenswelt Kommune mit Fokus auf strukturbildende Maßnahmen trägt entscheidend dazu bei, gesundheitliche Ungleichheit zu adressieren (Rütten & Gelius, 2011). Für einen substanziellen Public Health Impact bedarf es der Verbreitung von Ansätzen, die über geförderte Modellprojekte hinausgehen (WHO, 2010). Ziel des systematischen Reviews war es, eine Übersicht über Verbreitungskonzepte zu erstellen sowie Schlüsselkomponenten (SK) für die wirksame Verbreitung zu identifizieren. Mittels einer „Best Fit Framework Synthesis“ (Carroll et al., 2013) wurden zuerst evidenzbasierte Rahmenkonzepte der Verbreitung in den Datenbanken PubMed, CINAHL, Scopus, Web of Science, PsycInfo und SportDiscus gesucht. Daraus wurden a priori SK induktiv abgeleitet. Die gleichen Datenbanken sowie Google Scholar wurden anschließend nach Primärstudien zur Verbreitung kommunaler Bewegungsförderung durchsucht, welche anhand der a priori definierten SK deduktiv kodiert wurden. In 80 Artikeln wurden 12 Rahmenkonzepte identifiziert, wovon 5 für die Datenextraktion eingeschlossen wurden. Daraus resultierten 10 a priori SK: „Eigenschaften der Innovation“; „Rollen & Verantwortlichkeiten klären & koordinieren“; „Fähigkeiten, Wissen & Kapazitäten fördern“; „Ressourcen mobilisieren & sicherstellen“; „regelmäßige Kommunikation sichern“; „Assessment, Monitoring & Evaluation planen & durchführen“; „politische Unterstützung & Fürsprache entwickeln“; „Kooperationen aufbauen & erhalten“; „Partizipation & Eigenverantwortung fördern“ sowie „strategisches Vorgehen planen & umsetzen“. Aus 113 Primärstudien wurden 10 in die Analyse einbezogen, in der keine neuen SK ermittelt wurden. Es wurden wissenschaftlich fundierte Erkenntnisse für die erfolgreiche Verbreitung bewegungsbezogener Gesundheitsförderung identifiziert. Die SK werden in die Entwicklung eines wissenschafts- und praxisorientierten Verbreitungskonzepts einfließe

The Limitations and Potentials of Evaluating Economic Aspects of Community-Based Health Promotion: A Critical Review - Weber, Philipp; Birkholz, Leonie; Straub, Riccarda; Kohler, Simone; Helsper, Natalie; Dippon, Lea; Pfeifer, Klaus; Rütten, Alfred; Semrau, Jana (Applied Health Economics and Health Policy, 2024)
Community-based health promotion (CBHP) interventions are promising approaches to address public health problems; however, their economic evaluation presents unique challenges. This review aims to explore the opportunities and limitations of evaluating economic aspects of CBHP, focusing on the assessment of intervention costs and outcomes, and the consideration of political-level changes and health equity. A systematic search of the PubMed, Web of Science and PsycInfo databases identified 24 CBHP interventions, the majority of which targeted disadvantaged communities. Only five interventions included a detailed cost/resource assessment. Outcomes at the operational level were mainly quantitative, related to sociodemographics and environment or health status, while outcomes at the political level were often qualitative, related to public policy, capacity building or networks/collaboration. The study highlights the limitations of traditional health economic evaluation methods in capturing the complexity of CBHP interventions. It proposes the use of cost-consequence analysis (CCA) as a more comprehensive approach, offering a flexible and multifaceted assessment of costs and outcomes. However, challenges remain in the measurement and valuation of outcomes, equity considerations, intersectoral costs and attribution of effects. While CCA is a promising starting point, further research and methodological advancements are needed to refine its application and improve decision making in CBHP.<br

The Limitations and Potentials of Evaluating Economic Aspects of Community-Based Health Promotion: A Critical Review - Weber, Philipp; Birkholz, Leonie; Straub, Riccarda; Kohler, Simone; Helsper, Natalie; Dippon, Lea; Pfeifer, Klaus; Rütten, Alfred; Semrau, Jana (Applied Health Economics and Health Policy, 2024)
Community-based health promotion (CBHP) interventions are promising approaches to address public health problems; however, their economic evaluation presents unique challenges. This review aims to explore the opportunities and limitations of evaluating economic aspects of CBHP, focusing on the assessment of intervention costs and outcomes, and the consideration of political-level changes and health equity. A systematic search of the PubMed, Web of Science and PsycInfo databases identified 24 CBHP interventions, the majority of which targeted disadvantaged communities. Only five interventions included a detailed cost/resource assessment. Outcomes at the operational level were mainly quantitative, related to sociodemographics and environment or health status, while outcomes at the political level were often qualitative, related to public policy, capacity building or networks/collaboration. The study highlights the limitations of traditional health economic evaluation methods in capturing the complexity of CBHP interventions. It proposes the use of cost-consequence analysis (CCA) as a more comprehensive approach, offering a flexible and multifaceted assessment of costs and outcomes. However, challenges remain in the measurement and valuation of outcomes, equity considerations, intersectoral costs and attribution of effects. While CCA is a promising starting point, further research and methodological advancements are needed to refine its application and improve decision making in CBHP.
CRIS-Team Scopus Importer:2024-02-23

Von Erfolgsfaktoren, Hindernissen und Bedarfen zu Schlüsselkomponenten der kommunalen Bewegungsförderung bei Menschen mit sozialer Benachteiligung: Bericht von einem Workshop - Kohler, Simone; Semrau, Jana; Janz, Lukas; Helsper, Natalie; Abu-Omar, Karim; Pfeifer, Klaus; Rütten, Alfred (Bewegungstherapie und Gesundheitssport, 2019)

Welchen Einfluss hat politische Unterstützung auf die Implementierung der Nationalen Empfehlungen für Bewegung und Bewegungsförderung in einer ländlichen Kommune? Eine qualitative Fallstudie - Kohler, Simone; Helsper, Natalie; Dippon, Lea; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (Sport, Mehr & Meer – Sportwissenschaft in gesellschaftlicher Verantwortung. Abstractband des 25. dvs-Hochschultages, Kiel / virtuell, 29.–31. März 2022, 2022)

Welche Strukturen sind in Kommunen zur Förderung von Bewegung vorhanden? Eine vergleichende Fallstudie von sechs Modellkommunen in Deutschland - Helsper, Natalie; Dippon, Lea; Kohler, Simone; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (Sport, Mehr & Meer – Sportwissenschaft in gesellschaftlicher Verantwortung. Abstractband des 25. dvs-Hochschultages, Kiel / virtuell, 29.–31. März 2022, 2022)
Keywords: kommunale Bewegungsförderung; Strukturaufbau; Kontextanalyse

What Are Existing Structures in Communities for Physical Activity Promotion? A Comparative Case Study of Six Diverse Pilot Communities in Germany - Helsper, Natalie; Dippon, Lea; Kohler, Simone; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (24th IUHPE World Conference on Health Promotion, 2022)
Background The German National Recommendations for Physical Activity (PA) and PA Promotion recommend community-based PA promotion with a focus on health equity. To support the effective and sustainable implementation of this approach at the local level, a co-produced six-phase action-oriented framework with nine key components was tested in six pilot communities (PC). These PC varied in terms of their type (urban, rural), region, readiness, and socioeconomic deprivation. As communities are complex systems with dynamic relationships and interactions, a deeper understanding of the community’s context is crucial for the implementation. Therefore, the aim of this study is to analyse the initial context including existing structures in the six diverse PC. Methods Using a comparative case study design, we conducted and transcribed verbatim in total 32 qualitative interviews with key stakeholders from each PC including 7 political stakeholders, 6 experts, 8 representatives of the administration, 5 “door-openers” with contact to people with social disadvantages and 6 community facilitators (one per PC). We used purposive sampling to identify interviewees in the PC. The development of the semi-structured interview guideline was based on the co-produced nine key components. Our analysis draws on the approach of the qualitative content analysis. Results We will structure our in-depth analysis through comparing similarities and differences in the contexts of the six PC along the following nine key components: “political support”, “integrating existing structures”, “cooperation and intersectoral partnership”, “participation”, “communication”, “competencies and qualification”, “strategic planning/methodical approach”, “infrastructural/financial/personal resources and timeframe”, and “offers/programs”. A first exploration of our available data revealed differences between rural and urban communities in the key components “policy support” and “integrating existing structures”. Discussion A thorough analysis of the initial community context will contribute to a better understanding of the relationships between the process, output, and outcome of community-based PA promotion. Finally, it will support an enhanced exploration of the impact of this approach regarding sustainable structural change for PA promotion at the community level and improvement of health equity. <

What makes community-based, multilevel physical activity promotion last? A systematic review with narrative synthesis on factors for sustainable implementation - Helsper, Natalie; Dippon, Lea; Birkholz, Leonie; Rütten, Alfred; Kohler, Simone; Weber, Philipp; Pfeifer, Klaus; Semrau, Jana (PERSPECT PUBLIC HEAL, 2023)
Aim: To follow the need for more research and strategies to enhance the knowledge of sustainable implementation, we examined cases of community-based, multilevel physical activity-related health promotion after initial funding has ceased and aimed to identify factors that influence their sustainable implementation. Methods: Five scientific databases (PubMed; Scopus; Ebsco Host with CINAHL, PsychInfo, and Sportdiscus; ProQuest and Web of Science) were systematically searched for relevant literature in December 2021. Three reviewers performed a title/abstract screening and independently screened the full texts of the remaining papers, followed by a quality assessment. A narrative synthesis method, including qualitative text analysis, was used to synthesise retrieved articles. As starting point, the framework of Schell et al. containing nine domains for sustainability capacity was used and new emerging themes were inductively added. Results: The search revealed 270 potentially eligible articles out of 27,652 hits. After the systematic review process, 14 studies were included. In the synthesis, 14 factors influencing the sustainablity of community-based, multilevel physical activity-related health promotion were identified of which six are new factors compared to Schell et al. In particular, our findings bring forth a novel understanding of the importance of the factors ‘Participation and Partnerships’, ‘Empowerment and Capacity Building’ and ‘Community Support’. A dynamic interplay and high connectedness between factors were visible. Conclusion: The identified factors can help establish a better understanding of sustainability processes within whole-system approaches intervening on multiple levels in the community with the aim of systems change. They are relevant for practitioners, researchers and policy makers alike. Future research should more closely examine based on further theoretical elaboration how an interplay between the factors can promote sustainability and which interdependencies are of particular importance in facilitating sustainable and equitable change.
CRIS-Team Scopus Importer:2023-08-18
Keywords: community; health promotion; multilevel physical activity promotion; programme sustainability; systems change; whole-system approach

Wirksamkeit von kommunalen Maßnahmen zur Bewegungsförderung bei Menschen mit sozialer Benachteiligung. - Kohler, Simone; Semrau, Jana; Janz, Lukas; Helsper, Natalie; Abu-Omar, Karim; Rütten, Alfred; Pfeifer, Klaus (Sport im öffentlichen Raum. Abstractband des 24. dvs-Hochschultags von 18. bis 20. September 2019 in Berlin, 2019)
Einleitung Das Ausmaß körperlicher Inaktivität ist von sozialen Gradienten abhängig (1). Eine Vielzahl an Studien belegt, dass insbesondere Menschen mit sozialer Benachteiligung (MSB) zu wenig körperlich aktiv sind (2). Im Gegensatz dazu ist über den Erfolg kommunaler Bewegungsförderungsmaßnahmen bei MSB wenig bekannt. Im Rahmen eines systematischen Reviews war es das Ziel, die Wirksamkeit dieser Interventionen zu identifizieren. Methode In den Datenbanken Pubmed, Scopus, PsycInfo/SPORTDiscus (via Ebscohost), ERIC und IBSS (via Proquest) wurde für den Zeitraum 3/2015 bis 8/2018 nach Reviews gesucht, die sich mit der Wirksamkeit kommunaler Bewegungsförderungsmaßnahmen befassen und zwar unabhängig von der Zielgruppe. Ein zusätzliche Handsuche ergänzte die Recherche. Ergebnisse Im ersten Schritt wurden 1.997 Artikel identifiziert. Insgesamt konnten 20 Publikationen berücksichtigt werden, wobei sich nur sechs mit MSB befassten. In diesen Artikeln wurden insbesondere umweltbezogene Maßnahmen, Tailoring sowie die Einbeziehung der Zielgruppe als wirksam bei MSB beschrieben. Zusätzlich waren Strategien zur politischen Unterstützung, Strategien zur Intersektoralität und die Schaffung von Zugangswegen für MSB als Bedingung für die Wirksamkeit genannt. Diskussion Die aktuelle Forschungslage zu Bewegungsförderungsmaßnahmen von MSB im kommunalen Setting ist sehr begrenzt und die Studien von unterschiedlicher Qualität. Da die Zielgruppe MSB sehr weit gefasst ist, fallen die Belege für erfolgreiche Ansätze heterogen aus. Um die Wirksamkeit von Bewegungsförderungsmaßnahmen weiter beurteilen zu können, sind zusätzliche Studien notwendig, die sich auf die verschiedenen Gruppen von MSB in der Lebenswelt Kommune fokussieren. <br
Keywords: Bewegungsförderung; soziale Benachteiligung; Kommune; Wirksamkeit

Zugangswege von Menschen in schwierigen Lebenslagen in der kommunalen bewegungsbezogenen Gesundheitsförderung - Dippon, Lea; Helsper, Natalie; Kohler, Simone; Pfeifer, Klaus; Rütten, Alfred; Semrau, Jana (Jahrestagung dvs-Kommission Gesundheit, 2022)